The effects of thymoquinone as potential novel supplements theraphy for better outcome on methadone maintenance theraphy in opioid receptor expressing cell line (OREC) - Liyana Hazwani Mohd Adnan
Prolonged use of morphine progressively desensitizes opioid receptor expression on human cells. Subsequently, it causes dependency and tolerance in chronically exposed subjects. Dependency and tolerance are two main issues that cause big problems in managing opioid dependency. It is believed that the main mechanism of the above problems is mediated via calcium channels. Nigella sativa, through its main pharmacologically active compound, Thymoquinone (TQ), has been found to have calcium channel blocking ability and proven effective to reduce withdrawal symptoms among opioid dependent patients. However, to date, the supplement effects of TQ on methadone has not yet being studied. Thus this study is done to identify further roles of TQ as potential novel supplement therapy for better outcome for Methadone Maintenance Therapy in Opioid Receptor Expressing Cell or OREC using U87 MG cell line by looking at its cytotoxic activity, the regulating effects on cyclic Adenosine Monophosphate (cAMP) level, Mu-opioid receptor protein concentration and global differential expression of the genes (DEGs). U87 cells were grown in tissue culture flasks with RPMI 1640 medium containing I rnrnol/L L-glutamine, supplemented with 10% (v/v) fetal bovine serum, and 1% (w/v) penicillin/streptomycin. The cell viability was assessed by the trypan blue dye and manually counted using a haemocytometer. The MTT assay was used to determine the cytotoxic effects of Morphine and TQ. The protein concentration of human mu-opioid receptor (MOR) level and cAMP concentration in the cells were determined using the ELISA kit. Global DEGs was assessed by RNA Sequencing analysis. Statistical analysis was done using one-way analysis of variance (ANOVA) for grouped comparison followed by Dunnet's test. RNA Sequencing results were analysed using bioinformatic analysis. P-values less than 0.05 were considered statistically significant. It was shown that TQ presented lower cytotoxicity on OREC cells compared with morphine. Co-treatment of 61 ).1M TQ with morphine also signi ficantly attenuated the surge of cAMP contents produced by 35 ).1M morphine and significantly increased MOR protein concentration at 6h and 12h as compared to the cells treated with morphine alone (* P < 0.05). Global differential expression of the genes studied had indicated that TQ upregulated several key genes such as Phosphodiesterase (PDE), Gamma-arninobutyric acid (GABA) and G protein subunit genes. These findings suggested that TQ may compliment the effects of methadone in morphine addiction pathways via reducing the morphine-induced cAMP overshoot, increasing MOR protein concentration and upregulating PDE, GABA and G protein subunit genes.